Vancomycin resistant Enterococcus (VRE): Prevalence and characteristics in a tertiary hospital in Malaysia - Mohamed N.A.; Hussin H.; Chang K.M.; Hashim R.; Ahmad N. (Ministry of Health, 2024)
Indexed by Scopus